PERBANDINGAN KUALITAS HIDUP PASIEN PARKINSON SUBTIPE POSTURAL INSTABILITY GAIT DISORDER DAN SUBTIPE TREMOR DOMINAN DI RSI IBNU SINA PADANG - Lanang, A. S; Hamama, D. A; Prima Adelin (Nusantara Hasana Journal, 2024)
Background : Parkinson’s disease is a neurodegenerative disease associated with chronic onset and progressive motor symptoms.There are two types of motor disorders, Postural Instability Gait Disorder (PIGD) and Dominant Tremor (TD). Purpose : To compare level of quality of life of Parkinson’s patients with motor symptoms of PIGD and the TD in RSI Ibnu Sina. Methods : this research is unpaired numerical analytic with cross sectional study design.This study used the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) to identify subtypes of motor symtoms and The Parkinson’s Disease Questionnaire (PDQ-39) to assess quality of life. The bivariate was carried out using Independents T test. Results : Based on the results of the study, found that the age of Parkinson’s patients with PIGD and Dominant Tremor at RSI Ibnu Sina Padang was mostly 61-70 years old (47.8%), majority of the sexes were male (56.5%), and the longest suffering was <5 years (80.4%), the worst quality of life of Parkinson was found in the mobility domain with average score of 20.08, while the best quality was found in social support domain with average score of 0.15. P value = 0.000 mean PDQ-score 39 total between tremor subtypes (37.23) and PIGD (62.42) can affect the deterioration of quality of life in mobility domain, daily activities domain, and communication domain. There is difference between quality of life of Parkinson’s patients with the suptype PIGD and TD at Ibnu Sina Hospital, Padang.